Tense and Aspect in Ọ̀họ̀rí - Ọlaide AKINWANDE (ABUAD Journal of the Humanities-AGIDIGBO)
Reports in the linguistic literature indicate that inflection (Infl) is the layer that freezes elements like tense, aspect, agreement, modal, and negator and they are capable of projecting independent XO (Ilọri 2010). This article examines some functional categories such as tense [+TNS] and aspect [+ASP] in Ọ̀họ̀rí Yorùbá. Ọ̀họ̀rí is a dialect of Yorùbá which is spoken in Kétu and its environs in West Yorùbá (Oyelaran 1976; Adeniyi 2000), precisely in Yewa North Local Government Area of Ogun State, Nigeria. The data used in this study were elicited from eight adult native speakers of Ọ̀họ̀rí in Kétu, Ègùwà, and Asá in Yewa North Local Government Area of Ogun State, Nigeria via interviews using digital device. The analysis was done within the minimalist program of Chomsky (1993, 1995, 1998, and 2002) with Split Infl-hypothesis of Pollock (1989). The study shows that future tense and aspect are syntactically marked in Ọ̀họ̀rí. The paper further reveals that Ọ̀họ̀rí has a single element that marks both habitual and progressive aspects. The article proposes structures for the projection of TP and AspP in Ọ̀họ̀rí. The paper conclusively affirms that future tense markers can co-occur with perfective aspect marker in Ọ̀họ̀rí.